2016
DOI: 10.18869/acadpub.jafm.68.225.24454
|View full text |Cite
|
Sign up to set email alerts
|

The Hysteresis and Shear Velocity in Unsteady Flows

Abstract: The shear velocity is an important parameter in characterizing the shear at the boundary in open channels and there exist methods to estimate the shear velocity in steady flows, but the application and comparison of these methods to non-uniform unsteady flows is limited. In this study, three artificial triangular-shaped hydrographs were generated where the base flow is non-uniform with fine sand bed and the shear velocity was obtained by the methods, u*SV by using the Saint-Venant equations, u*L by using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
16
1
Order By: Relevance
“…Bed shear stress definition and measurement methods induce high uncertainty and difficulty in data interpretation. As each method of evaluation of the bed shear stress is uncertain to some extent, a comparison of a few methods may be helpful in interpreting the results as shown in other studies (Bombar, 2016;Qu, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bed shear stress definition and measurement methods induce high uncertainty and difficulty in data interpretation. As each method of evaluation of the bed shear stress is uncertain to some extent, a comparison of a few methods may be helpful in interpreting the results as shown in other studies (Bombar, 2016;Qu, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it should be noted that methods that may be applied under unsteady flow are scarce, mainly due to theoretical assumptions (Mrokowska et al, 2015a). Formulae derived from Saint-Venant model have become popular in unsteady flow experiments (Bombar, 2016;Song and Graf, 1996;Mrokowska et al, 2015b). However, the question about their applicability in evaluating bed shear stress under mobile bed conditions remains unanswered.…”
Section: Evaluation Of Bed Shear Stress and Stream Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The sound waves with high velocity were emitted from the core center of the instrument and the reflected waves were received by the three sensor arms. According to the Doppler principle, the velocity of flow was obtained [29]. The cylindrical sampling volume was 0.25 cm 3 and located 10 cm away from the sensor.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Hydraulic experiments have been designed to investigate the characteristics of unsteady flows as well as unsteady friction and shear stress [8,9]. For example, Sutter et al reported that the capacity of sediment transport increases when the unsteadiness of flow increases; this can be considered as the result of the effect of flow unsteadiness on shear stress [10].…”
Section: Introductionmentioning
confidence: 99%